Economics of Tobacco Toolkit, Tool 6 : Equity Issues, Tobacco, and the Poor - Peck, Richard M. (World Bank, Washington, DC, 2013)
Currently there are approximately 4 million tobacco related deaths annually. If present trends continue, by the year 2030 the number of deaths will soar to about 10 million annual deaths, with 7 million in low-income countries. However, government action to establish various tobacco control initiatives can prevent this from happening and save a significant number of lives. Tobacco control measures include: i) raising tobacco prices by imposing higher excise taxes; ii) advertising and marketing bans and restrictions; and iii) clean indoor air provisions. A popular and valid concern holds that raising tobacco excise taxes for the purposes of tobacco control imposes an untenable and unfair burden on the poor. In short, it is argued that higher tobacco excise taxes increase inequality in the post-tax distribution of income and reduces the real incomes of a particularly vulnerable group, the poor. This tool discusses a number of approaches in which to examine the validity of this argument. Techniques to analyze the impact of tobacco consumption and tobacco taxes on the poor are explained. And analytical methods using country-specific data are examined so that policy analysts can effectively address concerns about the poor, tobacco consumption, and tobacco control policies.